Impact Of Covid-19 Pandemic Among Medical Students In A Public University: A Study Protocol - Tengku Amatullah Madeehah Tengku Mohd; Amirah Binti Azzeri; Nurin Zaidi; Arni Affandi; Shasha Sheikh; Izlyn Izani; Amalin Muhammad; Syahidatul Sufyan; Sarah Saharudin; Adlina Anuar; Syazana Aisyah Azlan; Nurin Norhakimi; et al. (USIM Press, 2024)
ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences (Special Issue IHEC 02-2021) [June 2021]